Elimination of macrophages reduces glutaraldehyde‐fixed porcine heart valve degeneration in mice subdermal model - Zongtao Liu; Yixuan Wang; Fei Xie; Xing Liu; Fei Li; Nianguo Dong (Wiley, 2021)
Abstract Glutaraldehyde‐fixed porcine heart valve (GPHV) calcify and deteriorate over time. The aim of this study was to explore the roles macrophages play in mediating calcification and degeneration of the valve's connective tissue matrix. GPHV were implanted subcutaneously in the abdomens of C57BL/6 mice. The mice were equally divided into two study groups: (a) GPHV +phosphate buffered saline (PBS) liposomes, and (b) GPHV +clodronate liposomes. GPHV were collected for further analyses at 4 weeks post implant. Macrophages were almost depleted from the spleens of mice injected with clodronate liposomes as indicated by immunohistochemical staining. Furthermore, the expression of matrix metalloproteinase‐2 (MMP‐2), MMP‐9, and proinflammatory cytokines like IL‐1β, IL‐6, MCP‐1, MIP‐1a, MIP‐1b, were downregulated in the GPHV +Clodronate liposomal group compared with the GPHV+PBS liposomal group. Clodronate liposomal treatment led to significant decreases in the expression of RUNX2, ALP and OPN as well as less calcium deposits in GPHVs compared with PBS liposomal treatment. This finding indicated that infiltrating macrophages are critically involved in the development of calcification and deterioration in GPHVs. Macrophage depletion by clodronate liposomes decreased the extent of GPHV's calcification and deterioration.